Discovery and Community Dynamics of Novel ssRNA Mycoviruses in the Conifer Pathogen Heterobasidion parviporum - Sutela, Suvi; Piri, Tuula; Vainio, Eeva J. (Frontiers in Microbiology, 2021)
Heterobasidion species are highly destructive basidiomycetous conifer pathogens of the Boreal forest region. Earlier studies have revealed dsRNA virus infections of families Curvulaviridae and Partitiviridae of Heterobasidion strains, and small RNA deep sequencing has also identified infections of Mitoviridae members in these fungi. In this study, the virome of H. parviporum was examined for the first time by RNA-Seq using total RNA depleted of rRNA. This method successfully revealed new viruses representing two established (+)ssRNA virus families not found earlier in Heterobasidion: Narnaviridae and Botourmiaviridae. In addition, we identified the presence of a recently described virus group tentatively named “ambiviruses” in H. parviporum. The H. parviporum isolates included in the study originated from experimental forest sites located within 0.7 km range from each other, and a population analysis including 43 isolates was conducted at one of the experimental plots to establish the prevalence of the newly identified viruses in clonally spreading H. parviporum individuals. Our results indicate that viral infections are considerably more diverse and common among Heterobasidion isolates than known earlier and include ssRNA viruses with high prevalence and interspecies variation.